Metabolic activity in dormant conidia ofAspergillus nigerand developmental changes during conidial outgrowth - Novodvorska, Michaela; Stratford, Malcolm; Blythe, Martin J.; Wilson, Raymond; Beniston, Richard G.; Archer, David B. (Elsevier, 2016)
The early stages of development of Aspergillus niger conidia during outgrowth were explored by combining genome-wide gene expression analysis (RNAseq), proteomics, Warburg manometry and uptake studies. Resting conidia suspended in water were demonstrated for the first time to be metabolically active as low levels of oxygen uptake and the generation of carbon dioxide were detected, suggesting that low-level respiratory metabolism occurs in conidia for maintenance. Upon triggering of spore germination, generation of CO2 increased dramatically. For a short period, which coincided with mobilisation of the intracellular polyol, trehalose, there was no increase in uptake of O2 indicating that trehalose was metabolised by fermentation. Data from genome-wide mRNA profiling showed the presence of transcripts associated with fermentative and respiratory metabolism in resting conidia. Following triggering of conidial outgrowth, there was a clear switch to respiration after 25 min, confirmed by cyanide inhibition. No effect of SHAM, salicylhydroxamic acid, on respiration suggests electron flow via cytochrome c oxidase. Glucose entry into spores was not detectable before 1 h after triggering germination. The impact of sorbic acid on germination was examined and we showed that it inhibits glucose uptake. O2 uptake was also inhibited, delaying the onset of respiration and extending the period of fermentation. In conclusion, we show that conidia suspended in water are not completely dormant and that conidial outgrowth involves fermentative metabolism that precedes respiration.